2016
DOI: 10.18632/oncotarget.7084
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD44high/CD133high HCT-116 cells in the tumorigenesis of colon cancer

Abstract: This study aimed to explore cell surface biomarkers related to cancer stem cells (CSCs) and their role in the tumorigenesis of colon cancer. Various colon cancer cell lines were screened for CD133 and CD44 expression. CD44high/CD133high and CD44low/CD133low cells were separately isolated by Fluorescence-Activated Cell Sorting (FACS). The cell proliferation, colony formation, cell cycle characteristics, and tumorigenic properties in CD44high/CD133high and CD44low/CD133low cells were investigated through in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 33 publications
1
51
1
Order By: Relevance
“…Emerging evidence has shown that a subpopulation of cells, cancer stem cells (CSCs) or tumor-initiating cells, displays stem cell characteristics that influence tumorigenesis [2]. These cells possess specific properties, including self-renewal, differentiation potential, resistance to chemotherapy and high tumorigenicity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence has shown that a subpopulation of cells, cancer stem cells (CSCs) or tumor-initiating cells, displays stem cell characteristics that influence tumorigenesis [2]. These cells possess specific properties, including self-renewal, differentiation potential, resistance to chemotherapy and high tumorigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…CSCs have been prospectively identified in colorectal cancer by their expression of specific surface markers, such as leucine-rich-repeat-containing G-protein-coupled receptor 5 (Lgr5), CD133, CD44, CD166, EpCAM (epithelial cell adhesion molecule), CD24, CD29, and aldehyde dehydrogenase (ALDH), among others [2, 8-10]. More recently, it was reported that Lgr5 showed promise as a biomarker for colorectal CSCs [9, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is noteworthy that CD44 + and CD133 + stem cells have been documented in several human colon carcinoma-derived cell lines (31)(32)(33), and positive expression of these markers in colon carcinoma-derived HCT-116 cells have been correlated with the metastatic phenotype (31). In addition, as regards the upregulated expression of CD44 and c-Myc, supportive lines of evidence suggest that these Apc target genes are upregulated in colon cancer stem cells (20)(21)(22)(31)(32)(33). Furthermore, the SUL-R phenotype also raises the possibility that these resistant cells may display altered expression of non-COX targets, such as β-catenin, E-cadherin, mitochondrial apoptotic proteins, cyclin-dependent kinase inhibitor p21 WAF1/CIP1 and peroxisome proliferator-activated receptor-γ (PPAR-γ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that drug-resistant cancer stem cells have been isolated and characterized from colon carcinoma-derived cell culture models (31)(32)(33) and from luminal A and triple-negative breast carcinoma-derived cell culture models (43,44).…”
Section: Discussionmentioning
confidence: 99%